A dataset of clinically recorded radar vital signs with synchronised reference sensor signals - Schellenberger, Sven; Shi, Kilin; Steigleder, Tobias; Malessa, Anke; Michler, Fabian; Hameyer, Laura; Neumann, Nina; Lurz, Fabian; Weigel, Robert; Ostgathe, Christoph; Koelpin, Alexander (Scientific data, 2020)
Using Radar it is possible to measure vital signs through clothing or a mattress from the distance. This allows for a very comfortable way of continuous monitoring in hospitals or home environments. The dataset presented in this article consists of 24 h of synchronised data from a radar and a reference device. The implemented continuous wave radar system is based on the Six-Port technology and operates at 24 GHz in the ISM band. The reference device simultaneously measures electrocardiogram, impedance cardiogram and non-invasive continuous blood pressure. 30 healthy subjects were measured by physicians according to a predefined protocol. The radar was focused on the chest while the subjects were lying on a tilt table wired to the reference monitoring device. In this manner five scenarios were conducted, the majority of them aimed to trigger hemodynamics and the autonomic nervous system of the subjects. Using the database, algorithms for respiratory or cardiovascular analysis can be developed and a better understanding of the characteristics of the radar-recorded vital signs can be gained. Measurement(s) vital signs • Respiratory Rate • heart function measurement • Stroke Volume • blood pressure Technology Type(s) 24 GHz continuous wave radar • thoracic electrical bioimpedance (TEB) • electrocardiography • sphygmomanometry • impedance Sample Characteristic - Organism Homo sapiens Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.12613109